1983
DOI: 10.1007/bf00286646
|View full text |Cite
|
Sign up to set email alerts
|

A dominantly inherited cytogenetic anomaly: A possible cell division mutant

Abstract: Short-term lymphocyte cultures from three unrelated patients showed an increased frequency of mitoses with separated centromeres and splayed chromatids in the presence of colcemid. We refer to this phenomenon as premature centromere division (PCD). In two of the three patients the frequency of PCD in lymphocytes decreased when colcemid was omitted prior to harvest but was still higher than controls, whereas in the third patient, the frequency appeared unchanged. Cultured fibroblasts from the latter patient exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1

Year Published

1995
1995
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 13 publications
4
33
1
Order By: Relevance
“…The phenomenon we observed is similar to that which was found by Rudd et al (1983), Gabarron et al (1986), Madan et al (1987) and Fuster et al (1992) in that all the chromosomes of a cell were affected as well as the structural appearance of the chromosomes. However, it is apparently different from PCD, X (Fitzgerald 1975) in which only the X chromosome is involved, or from centromere splitting observed by German in 1979.…”
Section: Methodssupporting
confidence: 88%
See 2 more Smart Citations
“…The phenomenon we observed is similar to that which was found by Rudd et al (1983), Gabarron et al (1986), Madan et al (1987) and Fuster et al (1992) in that all the chromosomes of a cell were affected as well as the structural appearance of the chromosomes. However, it is apparently different from PCD, X (Fitzgerald 1975) in which only the X chromosome is involved, or from centromere splitting observed by German in 1979.…”
Section: Methodssupporting
confidence: 88%
“…This abnormal centromere behaviour can only affect one chromosome, as in the previously mentioned work; it can affect several chromosomes (Fitzgerald et al 1986), or it can involve all the chromosomes of a cell (Rudd et al 1983, Gabarron et al 1986, Madan et al 1987, Fuster et al 1992.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…PCD itself has been shown to segregate in autosomal dominant inheritance in some families (Rudd et al 1983;Madan et al 1987). Individuals with PCD were usually clinically normal, but there was sometimes an association with multiple spontaneous abortions or sterility (Rudd et al 1983;Gabarron et al 1986). Fitzgerald et al (1986) reported a clinically normal woman with three conceptuses with trisomy 21 who had PCD in some chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of one or more chromosomes with early or asynchronic separation of the centromere may be characteristic of a species or may result from the action of environmental agents (11)(12)(13)(14). In On, this phenomenon was more frequent at RF, suggesting that even if genetic factors are involved, the interpopulational variation observed must be influenced by outside factors (i.e., environmental agents).…”
Section: Articles • Environmental Genotoxicity Evaluationmentioning
confidence: 99%